Pricing methods in outcome-based contracting: δ3: reference-based pricing. (1st November 2020) - Alkhatib, Nimer S.; Erstad, Brian; Ramos, Kenneth; McBride, Ali; Bhattacharjee, Sandipan; Slack, Marion; Abraham, Ivo
Abstract: Aims: Six Delta is a six-dimensional independent platform for outcome-based pricing/contracting. The third dimension (δ3) estimates prices on the basis of international drug price referencing methods. We describe this dimension's methodology and present a proof-of-concept application to the treatment of non-small cell lung cancer (NSCLC) with EGFR mutation with osimertinib. Materials and methods: The reference-based pricing dimension utilizes a six-step method: (1) selecting foreign countries based on a set of four criteria (drug is available in the foreign country, price information is available in the foreign country, foreign countries are members within the organization for Economic Co-operation and Development, pricing methods in the foreign countries involve value assessment); (2) adjusting for exchange rates; (3) generating reference price (RP) scenarios; (4) adjusting with the medical inflation rate; (5) pooling all generated RP scenarios and calculating average and standard deviation (SD); (6) and Monte Carlo Simulation (MCS) to estimate the dimension-specific DSPReference . A proof-of-concept exercise with osimertinib in NSCLC was performed for two hypothetical outcome-based contracts: 1-year (2019–2020) and 2-year (2019–2021). Results: The United Kingdom and Canada met the four criteria. For the osimertinib 1-year contract price, the average of eight RP scenarios, adjusted for inflation by 0.44%, was $8, 892 (SD = $2, 606) for a 30-day prescription. MCS yielded a DSPReference estimate of $9, 395 or −35.72% of the wholesale acquisition cost (WAC) of $14, 616. For the 2-year contract, the average, adjusted for inflation by 0.72%, was $8, 928 (SD = $2, 610). MCS yielded a DSPReference estimate of $9, 442 or −35.40% of the WAC of $14, 616. Conclusions: We demonstrated that international price referencing methods can be integrated into our proposed Six Delta platform for outcome-based pricing/contracting.